PENGARUH BRAND IMAGE DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN DI MIXUE KOTA BIMA - syafitri, syafitri; Ernawati, Sri; Haryati, Intisari (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
Mixue It self is an ice cream and boba drink shop originating from China. This research aims to determine the significant influence of brand image and brand awareness on purchasing decisions at Mixue, Bima City. This type of research is associative using quantitative data. The population and sample in this study were 51 respondents using a purposive sampling technique. Data collection techniques include observation, literature study, and questionnaires. Data analysis techniques use validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, determination tests, t tests and f tests with the help of SPSS version 29 for Windows. The research results show that there is a significant influence of brand image and brand awareness on purchasing decisions at Mixue Bima City